LONELY OLD AGE IN SOCIAL GOVERNANCE: THE THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF SOCIOGERONTOLOGICAL ANALYSIS - Lobar Eryigitova (Western European Studies, 2025)
This article presents reflections on lonely old age within the system of social governance and the socio-gerontological analysis of working with the elderly, focusing on its theoretical and methodological foundations. In particular, the factors influencing the lives of elderly individuals in the modern era are examined through the perspectives and approaches of classical sociological theories
Keywords: demographic approaches; condition of loneliness; function of social life integration